Greening Growth in Pakistan through Transport Sector Reforms: A Strategic Environmental, Poverty, and Social Assessment - Sánchez-Triana, Ernesto (World Bank, 2015)
This book identifies reforms that can help manage environmental priority problems associated with transport?s impacts on air quality, noise pollution, road safety, hazardous-materials transport, climate change, and urban sprawl. The policy options are contextualized in light of the Government of Pakistan?s 2011 Framework for Economic Growth and its strategic objectives. Appendixes A?D present additional background information, describe the economic and institutional analyses undergirding this report, and detail the report?s methodology. This analytical work by a team of World Bank specialists focuses on: ? analyzing the policy and institutional adjustments required to address environmental, social, and poverty aspects of increased transportation efficiency in Pakistan; ? identifying policy options for the Government of Pakistan to better serve the population, to enhance social cohesion, and to foster equitable benefit sharing with low-income or other vulnerable groups; ? developing a broad participatory process to give a voice to stakeholders who could be affected by enhancements of freight transport productivity; and ? making robust recommendations to strengthen governance and the institutional capacity of agencies to manage the environmental, social, and poverty consequences of freight transportation infrastructure.